No Evidence of Rabies Exposure in Wild Marmosets (Callithrix jacchus) of Northeast Brazil - Benavides, Julio A. (2023)
Rabies transmitted by wildlife is the main source of human rabies mortality in Latin America and considered an emerging disease. The common marmoset Callithrix jacchus of Brazil is the only known primate reservoir of rabies worldwide. We tested whether alive free-ranging C. jacchus were exposed to rabies in four northeast states that have previously reported rabies-positive dead C. jacchus (Pernambuco and Bahia) or not (Paraíba and Rio Grande do Norte). Our results show no evidence of rabies antibodies or infection in the sampled C. jacchus, suggesting that apparently healthy marmosets are not widely exposed to rabies over their natural range.